2020
DOI: 10.1101/2020.09.01.277152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jumping back and forth: anthropozoonotic and zoonotic transmission of SARS-CoV-2 on mink farms

Abstract: The zoonotic origin of the SARS-CoV-2 pandemic is still unknown. Animal experiments have shown that non-human primates, cats, ferrets, hamsters, rabbits and bats can be infected by SARS-CoV-2. In addition, SARS-CoV-2 RNA has been detected in felids, mink and dogs in the field. Here, we describe an in-depth investigation of outbreaks on 16 mink farms and humans living or working on these farms, using whole genome sequencing. We conclude that the virus was initially introduced from humans and has evolved, most l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 52 publications
(31 reference statements)
2
92
0
6
Order By: Relevance
“…45,46,69 Together with chronology of infection, serologic evidence for infection with pH1N1 or COVID-19 in employees and workers in outbreak areas point out the occupational risk of human-to-animal transmission and vice versa. 10,46 Once the reverse zoonosis events occur, it is crucial to know whether infection is maintained in an animal population and has a potential to spillover back to humans. Therefore, continued serosurveillance in susceptible animals and other animal species in the same area are recommended.…”
Section: Epidemiology and Serological Surveillance In Reverse Zoonosimentioning
confidence: 99%
“…45,46,69 Together with chronology of infection, serologic evidence for infection with pH1N1 or COVID-19 in employees and workers in outbreak areas point out the occupational risk of human-to-animal transmission and vice versa. 10,46 Once the reverse zoonosis events occur, it is crucial to know whether infection is maintained in an animal population and has a potential to spillover back to humans. Therefore, continued serosurveillance in susceptible animals and other animal species in the same area are recommended.…”
Section: Epidemiology and Serological Surveillance In Reverse Zoonosimentioning
confidence: 99%
“…However, human SARS-CoV-2 cannot productively infect mice without extensive viral adaptation or introduction of human ACE2 into transgenic animals, and none of the mouse models supports transmission to uninfected mice 10 . Spillover of SARS-CoV-2 to farmed minks, subsequent large-scale mink-to-mink transmission and, in some cases, zoonotic transmission back to humans revealed efficient viral spread among members of the weasel genus without prior adaptation [11][12][13][14] . Although mink farms reported elevated animal mortality and gastrointestinal and respiratory clinical signs 15 , outbreak followup revealed continued intra-colony spread for extended periods of time 14 , suggesting that acute clinical signs in the majority of infected animals may be mild or absent.…”
Section: Main Textmentioning
confidence: 99%
“…Spillover of SARS-CoV-2 to farmed minks, subsequent large-scale mink-to-mink transmission and, in some cases, zoonotic transmission back to humans revealed efficient viral spread among members of the weasel genus without prior adaptation [11][12][13][14] . Although mink farms reported elevated animal mortality and gastrointestinal and respiratory clinical signs 15 , outbreak followup revealed continued intra-colony spread for extended periods of time 14 , suggesting that acute clinical signs in the majority of infected animals may be mild or absent. These mink field reports corroborated results obtained with experimentally infected ferrets showing that mustelids of the weasel genus transmit SARS-CoV-2 efficiently without strong clinical disease manifestation 16,17 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis showed that the mutated variants of SARS-CoV-2 virus were the same as those found in mink and were not identical to those found in unrelated SARS-CoV-2 patients living in proximity of the farms. 16 The World Organisation for Animal Health (OIE) has called on countries "to protect animal health and welfare, and consequently public health" and advised that actions should be taken to "Monitor susceptible animals, such as mink [
], as well as humans in close contact with them. Active monitoring is recommended as it might be difficult to detect early infections, especially [in] mink".…”
Section: Banning Fur Farming and The Fur Tradementioning
confidence: 99%